The role of demographics in small business loan pricing - Doris Neuberger; Solvig Räthke-Döppner (Universität Rostock, Institut für Volkswirtschaftslehre, 2014)
To sustain growth in an aging economy, it is important to ease the financing of small firms by bank loans. Using bank internal data of small business loans in Germany, we examine the determinants of loan rates in the period 1995-2010. Beyond characteristics of the firm, the loan contract, and the lending relationship, demographic aspects matter. However, collateral and relationship lending play a larger role in loan pricing than the entrepreneur's age. Banks do not seem to discriminate older borrowers by higher loan rates. We rather find statistical discrimination of younger borrowers because of their lower wealth. Single entrepreneurs obtain cheaper loans than married ones. Firms in peripheral regions with low population density are disadvantaged by higher loan rates compared to those in agglomerated regions.
Keywords: D14; E43; G21; J14; L26; 330; small business finance; savings banks; relationship lending; aging; demographic change